Pengembangan Personal Data Analitik Menggunakan PHP-ML dan Apache Spark pada IoT Cloud Apps - Ahmad Riyadh Al Faathin; Eko Sakti Pramukantoro; Fariz Andri Bachtiar (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
The Internet of things has systems and devices to monitor objects, collect and forward data. Diverse data will be collected using sensors then forwarded to stored in data storage. Data on IoT is generally low density data or does not have a lot of usefulness value if no analysis and visualization is carried out, besides that the data collected usually has specific goals and objectives according to user needs. Therefore we need a system that can store diverse data, perform data analysis and also personalize each IoT service needed. The researcher will focus the research on building a framework that is able to answer these problems, so that a data storage, analytic data and visualization webservice will be built in which a personal approach will be developed. System performance testing is done in terms of functional, scalability, response time for storing and retrieving data. The results of functional testing found that the framework system developed was running in accordance with its function in storing various data into data storage, performing data analysis and also personalizing service based on user needs. In addition, based on scalability testing that has been done shows that the system has a pretty good ability. Based on these results, this system can be a solution to IoT problems in the cloud